2023
DOI: 10.3390/polym15030747
|View full text |Cite
|
Sign up to set email alerts
|

Wood Surface Finishing with Transparent Lacquers Intended for Indoor Use, and the Colour Resistance of These Surfaces during Accelerated Aging

Abstract: This work evaluates the effects of accelerated aging on the discolouration of surface-treated spruce wood and oak wood coated with solvent-based polyurethane lacquers, and surface-treated spruce wood coated with water-based transparent coating systems. All concerned coating materials were intended for indoor use. It was also explored how the colour stability of spruce wood and oak wood surfaces treated with solvent-based polyurethane lacquers was affected by wood surface layer modifications with pigment or sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In our previous study [ 30 ], discolouration of a finishing system based on polyacrylic, and aldehyde resin resulted mainly from the photo yellowing of underlying untreated and HTT-treated wood due to sunlight and increased with irradiation time. Furthermore, the results of the study [ 46 ] showed that an accelerated ageing process with simulation of indoor conditions induced significant discolouration of surface-treated wood, both coated with solvent-based polyurethane and water-based lacquers. The spruce wood surfaces coated with solvent-based polyurethane lacquers were less stable than the oak surfaces treated in the same ways.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study [ 30 ], discolouration of a finishing system based on polyacrylic, and aldehyde resin resulted mainly from the photo yellowing of underlying untreated and HTT-treated wood due to sunlight and increased with irradiation time. Furthermore, the results of the study [ 46 ] showed that an accelerated ageing process with simulation of indoor conditions induced significant discolouration of surface-treated wood, both coated with solvent-based polyurethane and water-based lacquers. The spruce wood surfaces coated with solvent-based polyurethane lacquers were less stable than the oak surfaces treated in the same ways.…”
Section: Resultsmentioning
confidence: 99%
“…This would mean a common and interconnected influence of the two factors for each wood species and type of coating. A significant impact of wood species and type of lacquer/coating system, alongside pre-treatments of wood surfaces and modification of coatings, on the light-induced colour changes in wood surfaces was previously reported [59]. The interaction of the coating material with the wood substrate at the interface level, consisting in wetting and penetration, depending on both the structural features and surface properties of the substrate and the coating material, might be part of this significant twoway influence on the UV-induced colour changes determined in this research.…”
Section: Influence Of Wood Species and Coating Materials On The Light...mentioning
confidence: 95%
“…For instance, an increased protective effect of a 2 k polyurethane topcoat (based on hydroxyl-bearing polyacrylate and aliphatic poly-isocyanate) compared to an acrylic topcoat was reported for Radiata pine boards primed with a moisture curing isocyanate [58]. Colour change values ∆E varied in the range of approximately 2-10 units after 700 h light exposure (accelerated aging test simulating natural light passing through window glass) for spruce samples coated with four different three-layer coating systems (primer, middle layer, top layer) with waterborne coatings based on acryl/alkyd or polyurethane resins and their mixture [59].…”
Section: Influence Of Wood Species and Coating Materials On The Light...mentioning
confidence: 96%
“…It is important to point out that the topics of light-resistant clear coatings for indoor applications has been addressed less (Kúdela J. et al 2023) but it becomes increasingly important (Silverman C. 2016), as the market request for furniture and other wooden interior design elements with natural aspect is increasing. The influence of wood species (Oltean L. et al 2007), type of the clear coating materials (Aloui F. et al 2007(Aloui F. et al , Özgenç Ö. et al 2020, time and exposure / testing conditions (Kropat M. et al 2020), (Kanbayashi T. et al 2024) on the light induced colour changes of wood surfaces were addressed by worldwide research. Ultraviolet (UV) radiation from the natural light or artificial sources was recognised as the most aggressive ageing factor causing both colour and surface chemistry changes, but short wavelengths components of the visible light, in the violet (403nm) and blue range (434-496) may also contribute to the overall colour changes ), (Živković V. et al 2014).…”
Section: An Investigation Of the Influence Of Coating Film Thickness ...mentioning
confidence: 99%